Perkembangan Kapal Rekreasi dalam Perspektif Undang-Undang Pelayaran dan Implikasinya Terhadap Pengaturan Hukum dan Koordinasi Kelembagaan - Fatiyah Suryani Mile; R Lina Sinaulan; ST Laksanto Utomo; Adi Nur Rohman (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Recreational vessels represent an evolution of maritime tourism and shipping activities that are rapidly developing in Indonesia. However, from a legal standpoint, their status and regulation remain unclear. There is an overlap of authority between the Ministry of Tourism and the Ministry of Transportation, as well as disharmony between business classifications in the KBLI (Indonesian Standard Industrial Classification) and the national shipping licensing system. This article aims to analyze the legal status of recreational vessels within the maritime legislation system and its implications for legal certainty and implementation in practice. The method used is normative juridical, employing a statutory and document analysis approach. The findings indicate that recreational vessels still lack an explicit definition in Indonesia’s positive law, and their regulation is not yet harmonized between the maritime and tourism systems. Strengthened regulation and cross-sector harmonization are necessary to ensure legal certainty and support the growth of the marine tourism sector